The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/15563650.2014.923903
|View full text |Cite
|
Sign up to set email alerts
|

Barium toxicity and the role of the potassium inward rectifier current

Abstract: Barium is a potent, non-specific inhibitor of the potassium IRC current and affects all types of muscle at micromolar concentrations. Gastrointestinal symptoms frequently occur early in the course of barium poisoning. Hypokalemia resulting from an intracellular shift of potassium and the direct effect of barium at the potassium channels explain the cardiac arrhythmias and muscle weakness which commonly occur in barium poisoning. Treatment of barium poisoning is mainly supportive. Orally administered sulfate sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 76 publications
2
35
0
3
Order By: Relevance
“…Finally, hypokalaemia occurred, most likely resulting from an extra‐intracellular potassium shift. This findings strongly reflects the course seen in barium poisoning cases in man (Bhoelan et al, ). Interestingly, potassium administration to dogs counteracted most of the clinical signs (Roza and Berman, ).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, hypokalaemia occurred, most likely resulting from an extra‐intracellular potassium shift. This findings strongly reflects the course seen in barium poisoning cases in man (Bhoelan et al, ). Interestingly, potassium administration to dogs counteracted most of the clinical signs (Roza and Berman, ).…”
Section: Discussionsupporting
confidence: 83%
“…It has a high chemical reactivity and is never found in nature as a free element. It is highly toxic upon acute and chronic exposures (Bhoelan et al, 2014). Barium has been tested for its toxicity in different studies (Llugany et al, 2000;Langdon, 1994;Akinfieva and Gerasimova, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mechanism of barium ion poisoning resulting in hypokalemia is associated with the ability of the sodium potassium pump (Na + -K + -ATP enzyme) [5]. The Na + -K + -ATP enzyme is involved in transmembrane transport of potassium against concentration in intake within the cell.…”
Section: Discussionmentioning
confidence: 99%